2015
DOI: 10.5664/jcsm.5090
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Lithium Carbonate Supplemented with Nitrazepam on Sleep Disturbance during Cannabis Abstinence

Abstract: Study Objectives: Sleep disturbance is a hallmark feature of cannabis withdrawal. In this study we explored the effects of lithium treatment supplemented with nitrazepam on objective and subjective measures of sleep quality during inpatient cannabis withdrawal. Methods: Treatment-seeking cannabis-dependent adults (n = 38) were admitted for 8 days to an inpatient withdrawal unit and randomized to either oral lithium (500 mg) or placebo, twice daily in a double-blind RCT. Restricted nitrazepam (10 mg) was availa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 41 publications
1
18
0
Order By: Relevance
“…Acute cannabis withdrawal is a valid disorder, but far from being well understood. Withdrawal symptoms usually last up to 2 weeks; however, several studies reported continuation of these symptoms for 1–3 months with sleep being one of the consistently reported persisting withdrawal symptoms . In our review, none of the studies made a distinction between sleep disturbance as part of the withdrawal syndrome and cannabis induced sleep disorder as a separate phenomenon as described by DSM‐5 .…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…Acute cannabis withdrawal is a valid disorder, but far from being well understood. Withdrawal symptoms usually last up to 2 weeks; however, several studies reported continuation of these symptoms for 1–3 months with sleep being one of the consistently reported persisting withdrawal symptoms . In our review, none of the studies made a distinction between sleep disturbance as part of the withdrawal syndrome and cannabis induced sleep disorder as a separate phenomenon as described by DSM‐5 .…”
Section: Discussionmentioning
confidence: 78%
“…Cannabis withdrawal symptoms are most pronounced in the first 2 weeks post cessation, with some studies reported symptoms up to 12 weeks . Studies have shown that sleep difficulties occur in 67–73% of adults and 33–43% of adolescents following the cessation of chronic daily cannabis use . Symptoms reported by patients mainly include poor sleep quality, insomnia and strange dreams.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lithium carbonate was not helpful in managing sleep disturbances. 44 Gabapentin at 1200 mg per day improved withdrawal symptoms in a small study of adults and improved cognitive functioning. 45 In adolescents, emerging evidence seems to point to a role of Nacetyl-cysteine (NAC) in establishing abstinence.…”
Section: Treatment Of Withdrawalmentioning
confidence: 99%
“…12, 13 The onset of withdrawal is typically 24-48 hours after last use and peaks at 4-6 days. The total duration, as a result of the intense fat solubility of THC, is 1-3 weeks.…”
Section: Cannabis Withdrawalmentioning
confidence: 99%